The emotional statement: profile photo and self-branding in the art world. (7th July 2020) - Zhang, Yujia; Benayoun, Maurice
Along with the growing usage of the internet and social media, everyone has a new opportunity to construct a new identity - online identity. As one of the most significant channels of self-presence, profile photo contains more than facial features. It is rather the emotional statement. The art world is selected as the main object under inspection, as an ecosystem with distinctive subgroups. By studying the emotional structure of profile photos, we discover that artists show less happiness in the way of their online identity construction. We use the idea of self-branding to illustrate the phenomenon, as 'coolness' is a significant value for an artist. In a word, this paper has testified three hypotheses: 1) different emotional statements are for diverse career ecosystems; 2) for subgroups, emotional statements are customised to their target audiences; 3) artists pay more attention to 'self-construction' than 'pleasing the audience', and this could affect their degree of happiness.